Anti-clogging ability of the labyrinth emitter and its evaluation method - Zhang, Wenqian; Wang, Zhaoxi; Cheng, Senhao; Dong, Aihong; Zhang, Erxin; Niu, Wenquan (International Journal of Agricultural and Biological Engineering, 2022)
Emitter clogging is one of the most serious factors that restrict the drip irrigation systems operation and water use efficiency. To scientifically characterize and evaluate emitter clogging risk, a literature review, short-period emitter anti-clogging tests, and CFD (Computational Fluid Dynamics) hydraulic performance tests were conducted. Results showed that the emitter anti-clogging ability is related to its structure, material, and processing technology, not external factors. This was evidenced in the irrigation tests, as with the different water qualities, the same emitters were repeatedly prone to clog or to avoid clogging. A predictive model of structural resistance coefficient (Cs), a quantitative indicator of the emitter anti-clogging ability, whose value ranges between 0 and 1, was utilized. Larger Cs values indicate a lower anti-clogging ability and thus a higher risk of clogging. A good linear relationship between Cs and the relative flow rate was detected, and the Cs relationship with the fluidity index (x) was determined to be a power function. The Cs should be controlled within the range of 0.146-0.461 when designing new emitters to ensure that they have good anti-clogging properties. This research will provide theoretical guidance for the anti-clogging management of drip irrigation systems and for the design of optimal emitter structures.Keywords: drip irrigation system, structural resistance coefficient, emitter clogging risk, energy loss, anti-clogging abilityDOI: 10.25165/j.ijabe.20221506.6781Citation: Zhang W Q, Wang Z X, Cheng S H, Dong A H, Zhang E X, Niu W Q. Anti-clogging ability of the labyrinth emitter and its evaluation method. Int J Agric & Biol Eng, 2022; 15(6): 80–90.